Accidents with biological material in workers - Cleonice Andréa Alves Cavalcante; Elisângela Franco de Oliveira Cavalcante; Maria Lúcia Azevedo Ferreira de Macêdo; Eliane Cavalcante dos Santos; Soraya Maria de Medeiros (Universidade Federal do Ceará, 2013)
The objective was to describe the accidents with biological material occurred among workers of Rio Grande do Norte, Brazil, between 2007 and 2009. Secondary data were collected in the National Notifiable Diseases Surveillance System by exporting data to Excel using Tabwin. Among the types of occupational accidents reported in the state, the biological accidents (no. = 1,170) accounted for 58.3% with a predominance of cases among nurses (48.6%). The percutaneous exposure was the most frequent occurrence and the circumstances of the accidents were related to the handling of sharps and the most common organic material was blood (63.5%). More than 50% of the workers were vaccinated against hepatitis B, but without information regarding the evaluation of vaccine response. The study revealed the need of improvement in the quality of the information, once the sub-entries and inconsistencies make the National Notifiable Diseases Surveillance System less trustworthy in the characterization of the affected workers.